THE INCIDENCE OF PUBERTAL GYNECOMASTIA IN BOYS LIVING IN THE ANKARA REGION - GUVENC, H; YURDAKOK, M; KINIK, E; BUYUKGEBIZ, A (Turkish J Pediatrics, 1989)
The incidence of pubertal gynecomastia was determined in 646 Turkish body in Ankara [Turkey]. A marked increase in the incidence was observed at Pubertal Stage 4 (60.2%) and age 14 years (61.1%). The incidence of gynecomastia during puberty at various pubertal stages and ages was 34.6%. Although the incidence of unilateral gynecomastia was 19.6%; there was no difference between the right or left involvement.